Cost-effectiveness analysis of corticosteroid inhaler devices in primary care asthma management: A real world observational study - Linda Kemp; John Haughney; Neil Barnes; et al (Dove Medical Press, 2010)
Linda Kemp1, John Haughney2, Neil Barnes3, Erika Sims1, Julie von Ziegenweidt1, Elizabeth V Hillyer1, Amanda J Lee4, Alison Chisholm1, David Price1,21Research in Real Life Ltd, Old Winery Business Park, Cawston, Norwich, UK; 2Centre of Academic Primary Care, University of Aberdeen, Foresterhill Health Centre, Westburn Road, Aberdeen, UK; 3Department of Respiratory Medicine, London Chest Hospital, Bonner Road, London, UK; 4Medical Statistics Team, Section of Population Health, University of Aberdeen, Foresterhill, Aberdeen, UKPurpose: To evaluate and compare real world cost-effectiveness of inhaled corticosteroids (ICS) administered by metered dose inhaler (MDI), breath-actuated MDI (BAI), or dry powder inhaler (DPI) in asthma.Patients and methods: This retrospective database study analyzed the direct health care costs and proportion of patients (aged 5–60 years) achieving asthma control over 1 year in two population groups: those starting ICS (initiation population) and those receiving a first increase in ICS dose (step-up population). Asthma control was defined as no unplanned asthma visits, oral corticosteroids, or antibiotics for lower respiratory infection; outcomes were adjusted for confounding variables. Cost-effectiveness of BAI and DPI were compared with MDI.Results: For the initiation population (n = 56,347), average annual health care costs per person (adjusted results), as compared with MDIs, were £9 higher (95% CI: -1.65 to 19.71) for BAIs and £32 higher (95% CI: 19.51 to 43.66) for DPIs. The probability of BAIs being the dominant strategy (more effective and less costly than MDIs) was 5% and of BAIs being more effective and more costly than MDIs was 94%. DPIs were consistently more effective and more costly than MDIs, with an incremental cost-effectiveness ratio of £1711 (95% CI: 760 to 3,576) per additional controlled patient per year. For the step-up population (n = 9169), mean total health care costs per person, (adjusted) as compared with MDIs, were £1 higher (95% CI: -27.28 to 31.55) for BAIs and £73 higher (95% CI: 44.48 to 103.29) for DPIs. The probability of BAIs being dominant was 48% and of BAIs being more effective but more costly than MDIs was 52%; the probability of DPIs being more effective but more costly than MDIs was 96%.Conclusion: The real world effectiveness of ICS inhalers may vary, and inhaler device selection for patients with asthma should take into consideration not only initial device cost but also the subsequent health care resource costs.Keywords: asthma control, breath-actuated inhaler, dry powder inhaler, metered dose inhaler, incremental cost-effectiveness ratio